A systematic review of interventions to support transitions from intensive treatment for adults with anorexia nervosa and/or their carers. (9th March 2021) - Bryan, Danielle Clark; Cardi, Valentina; Willmott, Daniel; Teehan, Eimear Eileen; Rowlands, Katie; Treasure, Janet
Abstract: Aim: In the short term, intensive treatment focusing on restoring weight for anorexia nervosa can remediate many symptoms. However, there is a high level of relapse after discharge. This paper examines interventions developed to bridge the transition from intensive to less intensive forms of treatment for adult anorexia nervosa. Method: We undertook a systematic review of the literature on interventions aimed at providing transition support. The Template for Intervention Description and Replication was used to describe components of the transition interventions. Patient's drop‐out rates, weight, eating disorder psychopathology and mood data were extracted at end of treatment and follow‐up to describe preliminary efficacy. Results: Fourteen studies were selected: nine used psychological interventions delivered through face‐to‐face talking therapy or guided self‐help, three examined the use of fluoxetine and two assessed stepped‐care approaches. Transition support was delivered to patients in 11 studies, to patients and carers in two studies, and carers alone in another study. Conclusions: There was a great heterogeneity in the content and structure of the transition interventions evaluated. Overall, drop‐out rates were lower for psychological support than pharmacological interventions or stepped‐care approaches. Changes in eating disorder outcomes and mood were small to moderate throughout for studies that included a comparison group. Highlights: Psychological interventions to support the transition from inpatient care have good adherence The digital formats that have been piloted appear to be a feasible means to bridge the gap between specialist inpatient care and community care Medication (fluoxetine) and stepped‐care approaches are characterised by higher drop‐out rates